From Runway to Cityscape: Challenges of Airport-Driven Urban Growth - Bejrananda, Chakarin (International Journal of Building, Urban, Interior and Landscape Technology, 2024)
Incorporating airports into urban growth and economic development has greatly altered the geography and economics of cities. This study compares the conventional airports with the new model of the “Aerotropolis,” focusing on their dual functional nature as the points of entry and departure and growth drivers. It reviews the effects of airport growth on urban land use, the real estate market, and other economic sectors. The study uses examples from Schiphol Airport in the Netherlands and Dallas-Ft. Worth Airport in the United States. The analysis identifies the potential and challenges of the Aerotropolis approach as well as concerns on sustainability, equity, and the coherency of economic development with planning. It is recommended that to ensure effective economic development, there is a need to enhance governance, involve stakeholders and effectively manage land use to ensure that economic development is sustainable and beneficial to the environment and the people affected. This paper finds that airports can have a great impact on today’s urban and economic environments and highlights the need for a proactive and sustainable approach to the development of airport-related projects.